SISTEM PENDUKUNG KEPUTUSAN PENJUALAN KELAPA KEPADA TOKE DENGAN METODE SAW DI KELURAHAN SUNGAI PIRING - Siti Wardah; Kharisma Kurniawan; Muh. Rasyid Ridha (Indragiri Islamic University, 2022)
The process of selling coconuts that occurs in the Sungai Piring Village is that the farmers sell their coconuts to Toke and then Toke sells the coconuts to the company. For the Sungai Piring itself, there are 3 coconut Toke who buy coconut from the farmers with different prices and different requirements. So far, farmers sell their coconuts to Toke randomly, so a decision support system (DSS) is needed which is part of a computer-based information system including a knowledge-based system or knowledge management that is used to support decision making. The method used is Simple Additive Weighting (SAW) which is a weighted addition method to solve a problem. This is done so that the farmers can choose the best Toke to sell their coconuts in order to get a greater value.